Insights Into the Proteomic Profiling of Extracellular Vesicles for the Identification of Early Biomarkers of Neurodegeneration - Quiroz-Baez, Ricardo; Hernández-Ortega, Karina; Martínez-Martínez, Eduardo (Frontiers in Neurology, 2020)
Extracellular vesicles are involved in the development and progression of neurodegenerative diseases, including Alzheimer’s and Parkinson’s disease. Moreover, extracellular vesicles have the capacity to modify the physiology of neuronal circuits by transferring proteins, RNA, lipids, and metabolites. The proteomic characterization of extracellular vesicles (exosomes and microvesicles) from preclinical models and patient samples has the potential to reveal new proteins and molecular networks that affect the normal physiology prior to the appearance of traditional biomarkers of neurodegeneration. Noteworthy, many of the genetic risk associated to the development of Alzheimer’s and Parkinson’s disease affect the crosstalk between mitochondria, endosomes, and lysosomes. Recent research has focused on determining the role of endolysosomal trafficking in the onset of neurodegenerative diseases. Proteomic studies indicate an alteration of biogenesis and molecular content of extracellular vesicles as a result of endolysosomal and autophagic dysfunction. In this review, we discuss the status of extracellular vesicle proteomic characterization and their usefulness in discovering new biomarkers for the differential diagnosis of neurodegenerative diseases. Despite the challenges related to the failure to follow a standard isolation protocol and their implementation for a clinical setting, the analysis of extracellular vesicle proteome has revealed the presence of key proteins with post-translational modifications that can be measured in peripheral fluids.